2018
DOI: 10.1007/s13205-018-1204-4
|View full text |Cite
|
Sign up to set email alerts
|

First global transcriptome analysis of brown algae Macrocystis integrifolia (Phaeophyceae) under marine intertidal conditions

Abstract: To understand the physiological responses of the brown macroalga during the marine tidal cycle, two RNA libraries were prepared from algal frond samples collected in the intertidal zone (0 m depth) and subtidal zone (10 m depth). Samples collected from intertidal zone during low tide was considered as abiotic stressed (MI0), while samples collected from subtidal zone was considered as control (MI10). Both RNA libraries were sequenced on Illumina NextSeq 500 which generated approx. 46.9 million and 47.7 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Analyses of generation-biased gene expression used published RNA-seq datasets (at least two replicate samples) for gametophytes and sporophytes of the model brown alga Ectocarpus sp. [27, 31], S. japonica [25, 32] and M. pyrifera [27, 33]. For S. lomentaria , a published dataset was available for the gametophyte generation [31] and we generated RNA-seq data for duplicate samples of sporophytes (Additional file 1: Table S3 and “Methods” section for details).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of generation-biased gene expression used published RNA-seq datasets (at least two replicate samples) for gametophytes and sporophytes of the model brown alga Ectocarpus sp. [27, 31], S. japonica [25, 32] and M. pyrifera [27, 33]. For S. lomentaria , a published dataset was available for the gametophyte generation [31] and we generated RNA-seq data for duplicate samples of sporophytes (Additional file 1: Table S3 and “Methods” section for details).…”
Section: Resultsmentioning
confidence: 99%
“…All data generated or analysed during this study are included in this published article and its supplementary information files. The datasets generated and analysed in this article are available in the SRA repository under accession numbers: SRR6742570-71; SRR4446494-95, SRR5026349-55, SRR5026357, SRR5026360-63, SRR5026366, SRR5026588, SRR5026590-94 [27]; SRR1166427-30, SRR1166441, SRR1166452, SRR1660829-30, SRR5026364-65, SRR5026634-35 [31]; SRR5860560-68 [32]; SRR3544557, SRR3615022 [33]. Details of SRA references for sequence data are also included in Additional file 1: Table S3.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…2012, Salavarría et al. 2018). Altogether, our results conform to previous studies which demonstrated that antioxidant defense might be an important acclimation of brown macroalgae to environmental stress conditions.…”
Section: Discussionmentioning
confidence: 98%
“…The other gene regulations occurring after 48 h could be related to the accumulation and perception of cell wall degradation products, such as oligoalginates (Figure 4B). Indeed, some stress-response related genes were upregulated in S. latissima such as vanadium dependent bromoperoxidases (vBPO) and vanadium dependent iodoperoxidases (vIPO) involved in halide metabolism of brown algae and upregulated during abiotic and biotic oxidative responses (Cosse et al, 2009;Strittmatter et al, 2016;Salavarría et al, 2018). Other upregulated genes were putatively involved in calcium and oxylipin signaling pathways, two key pathways activated upon biotic and abiotic stress (Knight, 1999;Eckardt, 2008;Zhang et al, 2014).…”
Section: S Latissima Gene Expression Responses Were Mainly Related To the Activation Of Cell Wall Metabolismmentioning
confidence: 99%